2006
DOI: 10.1186/1472-6920-6-25
|View full text |Cite
|
Sign up to set email alerts
|

Learning to mark: a qualitative study of the experiences and concerns of medical markers

Abstract: Background: Although there is published research on the methods markers use in marking various types of assessment, there is relatively little information on the processes markers use in approaching a marking exercise. This qualitative paper describes the preparation and experiences of general practice (GP) teachers who undertake marking a written assessment in an undergraduate medical course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…As shown in Figs. 2 and 3 (and in Tables 4 and 5 ) above, the use of a ‘single screening’ approach would have resulted in the exclusion of one eligible study [ 22 ] from the ‘case study’ systematic review, while use of the ‘single screening with text mining’ approach would have resulted in the exclusion of eight other eligible studies [ 23 30 ]. Analysis of the contributions made by these nine ‘false negative’ studies to the ‘case study’ review found that all nine contributed only to the descriptive component of the review (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figs. 2 and 3 (and in Tables 4 and 5 ) above, the use of a ‘single screening’ approach would have resulted in the exclusion of one eligible study [ 22 ] from the ‘case study’ systematic review, while use of the ‘single screening with text mining’ approach would have resulted in the exclusion of eight other eligible studies [ 23 30 ]. Analysis of the contributions made by these nine ‘false negative’ studies to the ‘case study’ review found that all nine contributed only to the descriptive component of the review (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that the new task of formulating feedback in writing made the teaching more challenging. It has not only been found that teachers lack self-confidence in making assessments and giving feedback, but also that the rapid pace of ambulatory clinics reduces the opportunities for teaching and learning (Bowen & Irby 2002;Hawthorne et al 2006). Possibly, the StudentPEP project did not take the teachers' busy work in general practice seriously enough.…”
Section: Teachers' Feedbackmentioning
confidence: 99%